2015
DOI: 10.1002/elps.201500076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis using 2DE‐LC‐MS/MS reveals the mechanism of Fuzhuan brick tea extract against hepatic fat accumulation in rats with nonalcoholic fatty liver disease

Abstract: Fuzhuan brick tea has received increasing attention in recent years owing to its benefits for nonalcoholic fatty liver disease (NAFLD) and associated metabolic syndrome. For exploring the ameliorative mechanism, the liver proteomes from three groups of rats fed either a normal control diet (NCD), a high fat diet (HFD), or a HFD supplemented with high-dose Fuzhuan brick tea extract (FTE) (HFD + HFTE) were comprehensively compared by quantitative proteomics using 2DE-LC-MS/MS. This is the first study of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In recent years, a growing body of animal and human studies showed that dietary supplementation with tea was a potentially viable nutritional strategy for the prevention of obesity . It has been demonstrated that FBT and KDC consumption could prevent weight gain and metabolic disorders induced by HFD feeding . Furthermore, Lactobacillus johnsonii and another Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing body of animal and human studies showed that dietary supplementation with tea was a potentially viable nutritional strategy for the prevention of obesity . It has been demonstrated that FBT and KDC consumption could prevent weight gain and metabolic disorders induced by HFD feeding . Furthermore, Lactobacillus johnsonii and another Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In high fat diet‐fed rats, Fuzhuan tea reduced body weight and hepatic steatosis, and suppressed development of hypolipidemia . Another study demonstrated that rats consuming Fuzhuan tea with HFD showed protein expression consistent with reduced lipogenesis and enhanced β‐oxidation, tricarboxylic acid cycle, and electron transport when compared with HFD‐fed rats not receiving the tea . Finally, several studies have demonstrated inhibitory effects of Fuzhuan tea on enteric pathogens and one study showed stimulation of specific commensal organisms, including Lactobacilli .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the attention of Fuzhuan Brick‐Tea is considerable due to its benefits to human health, especially the anti‐obesity and hypolipidemic effects (Foster et al., 2016; Li et al., 2013; Liu et al., 2015). According to the latest report, the hypoglycemic effect of water extract from Fuzhuan Brick‐Tea was investigated in type II diabetic (Huang, Liu, Huang, Yang, & Qin, 2016).…”
Section: Introductionmentioning
confidence: 99%